PENGEMBANGAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN PROFESIONALISME GURU DI YAYASAN ASSHODIQIYAH SEMARANG - P, Toni Wijanarko A.; Fitrianto, Yuli; Solechan, Achmad; Kusumo, Haryo; Hakim, Fitro Nur (Universitas AMIKOM Yogyakarta, 2023)
ABSTRACT The implementation of this service activity is carried out for teachers at the Asshodiqiyah Semarang Foundation which includes orations, training and mentoring which are given directly and gradually. The activity was carried out for 2 days and was attended by 28 participants from teachers (elementary, junior high, MA, vocational) in the Semarang Asshodiqiyah Foundation and guided by 9 presenters / lecturers from the University of Computer Science and Technology. After holding community service activities in the form of orations and training for elementary, junior high, MA and vocational teachers in the Semarang Asshodiqiyah Foundation, it can be concluded that: The implementation of these community service activities was deemed successful in developing the creativity of teachers in developing interactive learning media because the majority of the participants attending training activities can create an interactive learning media in accordance with the subjects taught at school. The teachers seemed enthusiastic about participating in this training and hoped that similar activities could be held in the future to improve the skills and abilities of the teachers. Keywords: learning media, teacher professionalism ABSTRAK Pelaksanaan kegiatan pengabdian ini dilakukan kepada guru di Yayasan Asshodiqiyah Semarang yang meliputi orasi, pelatihan serta pendampingan yang diberikan secara langsung dan bertahap. Kegiatan tersebut dilaksanakan selama 2 hari dan diikuti sebanyak 28 peserta dari para guru (SD, SMP, MA, SMK) di lingkungan Yayasan Asshodiqiyah Semarang dan dipandu oleh 9 orang pemateri / dosen dari Universitas Sains dan Teknologi Komputer. Setelah diadakannya kegiatan pengabdian masyarakat berupa orasi dan pelatihan bagi para guru SD, SMP, MA dan SMK di lingkungan Yayasan Asshodiqiyah Semarang), dapat disimpulkan bahwa: Pelaksanaan kegiatan pengabdian ini dirasa berhasil dalam mengembangkan kreatifitas pengajar dalam mengembangan media pembelajaran interaktif karena mayoritas para peserta yang hadir dalam kegiatan pelatihan dapat membuat suatu media pembelajaran interaktif sesuai dengan mata pelajaran yang diampu di sekolah. Para pengajar nampak bersemangat dalam mengikuti pelatihan ini dan berharap kegiatan serupa dapat diadakan dikemudian hari untuk meningkatkan keterampilan dan kemampuan pengajar. Kata Kunci: media pembelajaran, profesionalisme guru